2006
DOI: 10.1038/sj.ki.5000100
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and impaired myocardial fatty acid metabolism in dialysis patients with normal coronary arteries

Abstract: We investigated whether insulin resistance is associated with impaired cardiac fatty acid metabolism in maintenance hemodialysis patients without coronary artery disease. We studied 55 nondiabetic (63+/-11 years old) and 51 diabetic (61+/-10 years old) hemodialysis patients with normal coronary arteries, using single-photon emission computed tomography (SPECT) with an iodinated fatty acid analogue, iodine-123-beta-methyl iodophenyl-pentadecanoic acid ((123)I-BMIPP), to evaluate cardiac fatty acid metabolism. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Dyslipidemia is also a common complication of CKD (5,6,24). We observed abnormally elevated plasma lipids and cholesterol in uremic rats, with parallel increases in lipogenic gene and protein expression.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Dyslipidemia is also a common complication of CKD (5,6,24). We observed abnormally elevated plasma lipids and cholesterol in uremic rats, with parallel increases in lipogenic gene and protein expression.…”
Section: Discussionmentioning
confidence: 71%
“…Dyslipidemia manifested by raised serum levels of triglycerides, free fatty acids, and cholesterol is observed in CKD patients and rodent models of uremia (5,6,24). Dyslipidemia can cause insulin resistance (25,26).…”
Section: Uremic Rats Develop Impaired Glucose Tolerance and Reduced Imentioning
confidence: 99%
See 1 more Smart Citation
“…HOMA-IR closely mirrors the clamp technique in the assessment of insulin sensitivity in subjects with various degrees of glucose tolerance and insulin sensitivity, also in type 2 diabetic patients treated with hypoglycemic agents [30,31]. HOMA-IR has also been applied to nondiabetic patients: with end-stage renal disease [32,33], treated with IHD [33][34][35][36][37][38][39][40][41][42] or peritoneal dialysis [42][43][44][45][46]. Shoji et al [47] demonstrated the usefulness of HOMA-IR to assess insulin resistance in renal failure patients; they also included insulin users into the study.…”
Section: Discussionmentioning
confidence: 98%
“…The price of this switch in metabolism is a less efficient ATP production, even though less oxygen is required for its synthesis. Investigators have used single-photon emission computed tomography with the fatty acid analogue iodine-123-β-methyl iodophenyl-pentadecanoic acid to demonstrate alterations in myocardial fatty acid utilization in end-stage renal disease patients (without coronary artery disease), which was strongly correlated with systemic glucose intolerance and systolic left ventricular dysfunction [31]. In another study, impaired myocardial fatty acid metabolism in asymptomatic patients with end-stage renal disease was able to identify the subgroup of patients who were at high risk for cardiac death [15].…”
Section: Discussionmentioning
confidence: 99%